Automatisierung und Arbeit in der Automobilindustrie Von Henry Ford zur Industrie 4.0 - Jürgens, Ulrich (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Against the backdrop of the discussion on Industry 4.0, this book investigates the car industry's experiences with automation so far and its impact on work. The book's examination of developments at Ford, Toyota and Volkswagen over the past 100 years generates surprising insights into automation processes and their influencing factors. The book opposes technology-centred and monocausal approaches to explaining transformation processes and simplified ideas about the consequences of automation. It combines micro-analyses of automation processes at plant level with an analysis of overarching trends in automation, productivity and changes in working conditions and activity structures.